Diarylpentanoid (1,5-bis(4-hydroxy-3-methoxyphenyl)-1,4-pentadiene-3-one) (MS13) Exhibits Anti-proliferative, Apoptosis Induction and Anti-migration Properties on Androgen-independent Human Prostate Cancer by Targeting Cell Cycle–Apoptosis and PI3K Signalling Pathways - Abd. Wahab, Nurul Azwa; Abas, Faridah; Othman, Iekhsan; Naidu, Rakesh (Frontiers in Pharmacology, 2021)
Diarylpentanoids exhibit a high degree of anti-cancer activity and stability in vitro over curcumin in prostate cancer cells. Hence, this study aims to investigate the effects of a diarylpentanoid, 1,5-bis(4-hydroxy-3-methoxyphenyl)-1,4-pentadiene-3-one (MS13) on cytotoxicity, anti-proliferative, apoptosis-inducing, anti-migration properties, and the underlying molecular mechanisms on treated androgen-independent prostate cancer cells, DU 145 and PC-3. A cell viability assay has shown greater cytotoxicity effects of MS13-treated DU 145 cells (EC50 7.57 ± 0.2 M) and PC-3 cells (EC50 7.80 ± 0.7 M) compared to curcumin (EC50: DU 145; 34.25 ± 2.7 M and PC-3; 27.77± 6.4 M). MS13 exhibited significant anti-proliferative activity against AIPC cells compared to curcumin in a dose- and time-dependent manner. Morphological observation, increased caspase-3 activity and reduction of Bcl-2 protein levels in these cells indicated that MS13 induces apoptosis which is time- and dose-dependent. Moreover, MS13 effectively inhibited the migration of DU 145 and PC-3 cells. Our results indicate that cell cycle – apoptosis and PI3K pathways were the topmost significant pathways impacted by MS13 activity. Our findings suggest that MS13 may demonstrate anti-cancer activity by modulating DEGs associated with the cell cycle–apoptosis and PI3K pathways, thus inhibits cell proliferation, and cell migration as well as induce apoptosis in AIPC cells.